Java and Batak Rajawi Spiritual Human - Liber Siagian; Yakobus Ndona (Randwick International of Social Science Journal, 2023)
This article described about the Javanese and Batak Rajawi man. This article intends to compare the mindset of people from both tribes, backgrounds, and the impact on life. Data was collected through observation, interviews and document collection. The collected data were analyzed using Paul Recouer's hermeneutic circle. The results of the analysis show that the Java man is a spiritual man by relying on the "higher nature" as a protector, while Batak man shows more of a Rajawi man by emphasizing prosperity. The comparison shows that the two human patterns require synergy to build a good Indonesia.